AFM study of Ni- and Cu-doped Li2B4O7 lass surface - Adamiv, V. T.; Bolesta, I. M.; Burak, Ya. V.; Kushnir, O. O.; Karbovnyk, I. D. (Видавництво Львівської політехніки, 2012)
The results of atomic force microscopy (AFM) studies of surface of the lithium tetraborate glasses doped with Cu, Ni and annealed in the hydrogen (H2) atmosphere are presented.
Keywords: AFM; borate glasses; surface